Weaknesses of contemporary management methods in the opinion of managerspractitioners - Kaczmarek Bogusław (Management, 2018)
Weaknesses of contemporary management methods in the opinion of managers-practitioners The article analyzes two issues: a short description of the most important (according to the author) 15 contemporary management methods and the presentation of the opinion of the group of 18 top managers of medium and large enterprises from the Lodz region, nominated by local governments for the Lodz Voivodship Economic Award in the year 2017 on “knowledge and practical use of modern management methods”.